Analisis Penggunaan Mata Uang Asing Dalam Perjanjian Jual Beli Di Indonesia Berdasarkan Syarat Sah Perjanjian - Ivanov, Irsandi; Lestari, Rika; Dasrol, Dasrol (Peneliti.net, 2024)
The case of people in border areas who still use payment transactions in foreign currency is the people of Nunukan Regency, North Kalimantan, specifically the people of Krayan District, which borders Sarawak, Malaysia. Nunukan Regency is located in the northernmost region of North Kalimantan Province. This district borders directly with the state of Sabah (East Malaysia) to the north, with Bulungan and Malinau districts to the south, to the south with the state of Sarawak (East Malaysia) and to the east with the Sulawesi Sea. Nunukan Regency, which was inaugurated as an autonomous region in 1999, occupies an area of 14,247.50 km2. The applicable currency is not only Rupiah, it also uses Ringgit. The type of research used is normative research on legal principles, namely the principle of legal certainty, so research on legal principles is carried out on legal rules, which are standards for inappropriate behavior or behavior. This research can be carried out on primary and secondary legal materials. The data sources used in this research are secondary data, namely data obtained from literature studies and have binding legal force, consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data collection technique used by the author in this research is using library research, namely researching reading sources related to the topic in this research such as: law books, statutory regulations, court decisions related to research, opinions of scholars and other supporting materials. Based on the results of the research and discussion, it can be explained as follows: First, the validity of buying and selling using foreign currency in Indonesian territory is based on the legal conditions of the agreement, violating the legal conditions of the agreement contained in Article 1320 of the Civil Code, namely not fulfilling halal reasons. That by using foreign currency, it means violating Law Number 7 of 2011 concerning Currency. Second, The impact of the use of foreign currency on society in Indonesia can be summarized into several parts, namely: Legal impact: Imprisonment for a maximum of 1 (one) year and a maximum fine of IDR 200,000,000.00. The civil legal impact is that because the principal of the agreement and the legal conditions are not in accordance with statutory regulations, the agreement made by the people of the border area is considered null and void. The impact from an economic perspective is depreciation of the currency value which makes the bargaining value of the Rupiah low which can increase the price of local goods and affect foreign debt payments, which leads to increasingly worse social inequality. The impact in terms of domestic security will be crimes that have economic reasons, because the state fails to maintain economic stability.